2001
DOI: 10.2460/ajvr.2001.62.595
|View full text |Cite
|
Sign up to set email alerts
|

Amidolytic heparin activity and values for several hemostatic variables after repeated subcutaneous administration of high doses of a low molecular weight heparin in healthy dogs

Abstract: Heparin plasma activity was only slightly higher than that recommended for LMWH treatment of humans, and none of the dogs had signs of increased bleeding. Thus, administration of heparin in accordance with this dosing regimen can be recommended for use in clinical studies. The screening tests investigated were not suitable for use in monitoring LMWH treatment of dogs. Assays that use chromogenic substrates are necessary to reliably monitor LMWH plasma concentrations in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 20 publications
(27 reference statements)
2
31
0
Order By: Relevance
“…In a study by Mischke et al, 19 peak anti‐FXa activity 2 hours after a single injection of 100 U/kg to dogs in vivo was 0.43 U/mL of plasma. With repeated SC injections of 150 U/kg dalteparin every 8 hours, plasma anti‐FXa activity was 0.77 U/mL of plasma and 0.82 U/mL at 2 hours after the third and sixth injections 20 . The supratherapeutical concentrations pose a limitation in the present study with regard to the direct clinical applicability of the results, and further evaluations of the heparinase‐modified, TF‐activated TEG assay with doses in the recommended clinical range, followed by prospective clinical studies, are required to assess the performance and usefulness of heparinase‐modified, TF‐activated TEG in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Mischke et al, 19 peak anti‐FXa activity 2 hours after a single injection of 100 U/kg to dogs in vivo was 0.43 U/mL of plasma. With repeated SC injections of 150 U/kg dalteparin every 8 hours, plasma anti‐FXa activity was 0.77 U/mL of plasma and 0.82 U/mL at 2 hours after the third and sixth injections 20 . The supratherapeutical concentrations pose a limitation in the present study with regard to the direct clinical applicability of the results, and further evaluations of the heparinase‐modified, TF‐activated TEG assay with doses in the recommended clinical range, followed by prospective clinical studies, are required to assess the performance and usefulness of heparinase‐modified, TF‐activated TEG in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The human therapeutic target for AXa was not met for any dog in the LDH or DP groups. Because of these disparities, future studies with LMWH should be designed to evaluate the heparin activity produced by higher doses than the dose of DP that was used here, as originally suggested by Mischke 33 based on work in healthy dogs. If UFH is used in clinical studies, the HDH protocol is indicated but requires close therapeutic monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy with LMWH is associated with fewer complications such as heparin‐induced thrombocytopenia and requires less monitoring due to the standardized dose and predictable response in humans. Success with this product in human medicine has prompted interest in studying the use of LMWH in dogs for the prevention of venous thrombosis 33 …”
Section: Introductionmentioning
confidence: 99%
“…LMWH may also lower the risk of bleeding side‐effects because it shows more specific activity against coagulation factor Xa 33 . Several dosing regimes for LMWH administration in dogs have been suggested, from 100 IU/kg once a day to 150 IU/kg 2 or 3 times a day, depending on the LMWH used, the therapeutic goal, and the patient's clinical status 10,34–36 . Reduced LMWH doses and routine monitoring are advised in human renal failure patients, because the anti‐factor Xa activity of LMWH is strongly correlated with creatinine clearance 33 .…”
Section: Discussionmentioning
confidence: 99%